1966
DOI: 10.1111/j.1399-3054.1966.tb07090.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Apical Dominance to the Nutrient Accumulation Pattern in Pisum sativum var. Alaska

Abstract: Decapitation of the pea plant resulted in the growth of all the lateral shoots. The initial growth of all lateral buds was somewhat similar. The differential growth rates developed later on. The pattern of growth of lateral shoots varied with the age of the plant when decapitation was performed. The basal shoots dominated when the plants were decapitated at the 2‐leaf stage. At 3‐leaf stage decapitation resulted in the dominance of shoot 5. Decapitation at 4‐or‐more‐leaf stage resulted in the eventual dominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…how far the bud is from the site of decapitation; Fig. 2; Husain and Linck, 1966). This pattern of outgrowth is likely due to the bud at node 2 having a better established vasculature connection or being larger than other buds, enabling it to respond quickly when triggered, which subsequently allows it to induce correlative inhibition over other buds.…”
Section: Reduced Iaa Levels In the Main Stem Do Not Trigger Bud Outgrmentioning
confidence: 99%
“…how far the bud is from the site of decapitation; Fig. 2; Husain and Linck, 1966). This pattern of outgrowth is likely due to the bud at node 2 having a better established vasculature connection or being larger than other buds, enabling it to respond quickly when triggered, which subsequently allows it to induce correlative inhibition over other buds.…”
Section: Reduced Iaa Levels In the Main Stem Do Not Trigger Bud Outgrmentioning
confidence: 99%
“…1B). Other investigators have found that rapid growth of a bud can inhibit buds at higher and lower nodes in pea (11) and at opposite nodes of Alternanthera, a decussate plant (6). However, a detailed study of the transition from growth to dormancy, as we have described for small axillary buds of pea, has not been reported previously (Fig.…”
Section: Axillary Bud Growthmentioning
confidence: 99%
“…sativum plants in which basal branches and /or buds are present (Hussain and Linck 1966;King and van Staden 1988;Ferguson and Beveridge 2009). The present results show,…”
Section: Variation In Bud Outgrowth Potentialmentioning
confidence: 99%
“…This is particularly apparent in annual species, such as Pisum sativum (Hussain and Linck 1966;King and van Staden 1988), and in response to nodal rooting in prostrate clonal herbs (Thomas et al 2014). In both cases an initial phase of bud outgrowth to form a highly branched basal zone on the shoot is followed by a phase in which bud outgrowth is suppressed to form an 'inhibition zone' (Weberling 1989).…”
Section: Introductionmentioning
confidence: 99%